Acute Diarrhea Disease (ADD) Outbreak Investigation at Kebumen, Central Java, Indonesia : Bayu Satria Wiratama, Tutik Inayah Susilaningsih, Yusrizal, Muhammad Fadhil, Akhmad Mukhibin, Joao Manuel Correia Ximenes - Bayu Satria Wiratama; Tutik Inayah Susilaningsih; Yusrizal; Muhammad Fadhil; Akhmad Mukhibin; Joao Manuel Correia Ximenes (STIKes Persada Husada Indonesia, 2026)
Research Objective: On January 21, 2022, an increasing number of ADD with one infant death was reported from rural area Karangtanjung village, Kebumen district. An investigation was initiated to confirm, describe, and recommend measures for control. Methodology: A 1:4 unmatched case-control study was conducted. Cases were defined as person who had three or more loose watery stools per day in Karangtanjung between January 16 and 29, 2022. Controls were people who had no diarrhea symptoms. Clean water source samples were collected for bacteriological testing. Stools samples were no longer available during the investigation. The risk factors and environmental data were obtained through interviews and observation using questionnaires. The data were analyzed using logistic regression for multivariate. Results: There were a total of 100 participants, 20 cases and 80 controls. Most of the cases (55%) were female, three children hospitalized (15%), and one infant death. The median age was four years old. Infants have the highest attack rate (AR =100%). While in control groups, 55% were male, the median age was 36.5 years old. Of the four clean water source samples, 3 (75%) were positive for faecal coliform and exceeded the standard quality of clean water sources. From multivariate analysis with logistic regression, only the 0–5 years age category (OR 14.33; 95% CI: 1.14–179.71) was significantly related to ADD. Conclusion: An outbreak of ADD was confirmed in Karangtanjung and was likely associated with a clean water source contaminated by groundwater. The 0-5 years age category was a significant risk factor for ADD. Several protective measures could be prepared, such as promoting hygiene and sanitation practices also recognizing early symptoms of diarrhea. Providing chlorine (calcium hypochlorite) 65% was recommended for control.